Ultimum Remedium in Law Enforcement of Large-Scale Social Restrictions in Indonesia during the Covid-19 Pandemic - Imam Pratama Rifky (Fakultas Hukum Universitas Lampung, 2021)
The new variant of corona virus from Wuhan is indeed very infectious. The Covid-19 has shocked the world because it is so deadly and takes many lives. So this has a significant impact on each country. Indonesia, to tackle the spread of this virus, has also implemented several ways, namely by encouraging people to live clean and healthy lives, implementing the 5M (Wearing masks, Washing hands, Keeping a distance, Staying away from crowds, Limiting mobilisation and interaction) and imposing restrictions. The government's efforts are solely for the common good. However, it is undeniable the large-scale social restrictions or Pembatasan Sosial Berskala Besar (PSBB) implementation also has an unfavourable impact on the community because their movement is restricted. This indirectly also harms the people's economic movement. So there are still some people who violate this PSBB rule. This study was conducted to determine whether the ultimum remedium is applied in law enforcement for PSBB violations. The research will use qualitative research by collecting data and news analyzation. The study results show that the government applies criminal sanctions and fines as an alternative to deter people.